Factors Affecting the Event of Stunting in Children Age to 24-59 Months in Centro Saude Internamento Gleno, Municipiu Ermera, Timor-Leste - Angelo Lafo Colo; Stefanus P. Manongga (Rifa'Institute, 2022)
Stunting is a developmental disorder in children caused by poor nutrition, repeated infections, and inadequate psychosocial stimulation. There are several factors that can cause stunting in children under five, such as family and socioeconomic characteristics. The purpose of this study was to determine the factors that influence the incidence of stunting in children aged 24-59 months. This research is quantitative research with a cross-sectional study design. The total population is 3,747 households, while the total sample is 110 which is divided proportionally from 7 villages (Sucos) which are included in the working area of the centro saude internamento Ermera. Based on the results of existing research, shows that there is an influence between children's eating patterns (? = 0.24), family income (? = 0.034), children's health care patterns (? = 0.037), and food consumption patterns in the family (? = 0.024) to the incidence of stunting. Meanwhile, family size (?=0.392), mother's education (?=0.360), and health condition (?=0.419). There is no effect on the incidence of Stunting. Interventions are needed to focus on several factors that trigger stunting problems in children under five so that they do not interfere with the growth and development process of children under five. It also requires high awareness through outreach activities to the community on the importance of child nutrition parenting and food consumption patterns in the family.